Penicillium roqueforti: an overview of its genetics, physiology, metabolism and biotechnological applications. Issue 2 (June 2020) - Coton, Emmanuel; Coton, Monika; Hymery, Nolwenn; Mounier, Jérôme; Jany, Jean-Luc
Abstract: Besides research on the model fungal genera Saccharomyces, Neurospora and Aspergillus, that has provided important biological knowledge in the areas of genetics, cell biology and physiology, recent investigations on non-model fungi used for food production offer insight into the mechanisms involved in food production but also adaptation and domestication processes. In this context, Penicillium roqueforti has been the most extensively studied species. This species is best known worldwide for its technological use for blue-veined cheese production and ripening. Recently, several advances related to taxonomy, population genetics, physiology and metabolism have been documented and provided deeper knowledge about this species. The methodological approaches used to study this species can be applied to other still largely understudied fungi associated with food production worldwide (e.g. P. camemberti, P. nalgiovense, P. salami i, Bisifusarium domesticum, Mucor spp.).